How expensive is vole damage? - Walther, B.; Fülling, O.; Malevez, J.; Pelz, H.-J. (Fördergemeinschaft Ökologischer Obstbau.e.V., D-Weinsberg, 2008)
Vole species, especially Arvicola terrestris and Microtus arvalis cause significant economical damage in organic pomiculture by gnawing the root system of trees. The importance of voles as pest organisms is well known. Nevertheless, the estimation of financial loss caused by voles is difficult for German fruit growers. We conducted a survey among organic fruit growers to get data on kind and amount of annual damage. Using the available publications and official statistics we calculated economical values of organic apple trees for different types of orchard processing and tree ages. Furthermore we calculated the number of trees lost due to voles in one year.